THE DISCOVERY OF CHALCORANA MEGALONESA IN JAVA AND THE EVALUATION OF ITS TAXONOMIC STATUS - Sabinhaliduna, Efendi; Arisuryanti, Tuty; Hamidy, Amir (Treubia, 2025)
Chalcorana chalconota was firstly described as Hyla chalconotus Schlegel from Java, and widely recognized as Rana chalconota Boulenger. This ranid frog species has widespread distribution in Southeast Asia. Molecular studies revealed that Rana chalconota is a complex species and consisted of several cryptic species. Among Sundaland population, this group was split into five species (C. chalconota sensu stricto, C. parvaccola, C. rufipes, C. raniceps, C. megalonesa), and together with C. labialis and C. eschatia, they nested in a monophyletic group. During herpetological survey in West Java, we collected two morphotypes of Rana chalconota from Pasir Angin, Bogor and evaluated their taxonomy status using morphology approach and molecular data with 16S rRNA mitochondrial gene. The results revealed two morphotypes belong to C. chalconota sensu stricto and C. megalonesa. The genetic distance of C. megalonesa between Java population and Sarawak (Borneo) population ranged from 2.4 to 2.6% that still below the threshold of species delimitation on the 16S rRNA gene. Therefore, these two populations are conspecific. This discovery of C. megalonesa in Java has contributed to increase the number of species of amphibians in Java to become 46 species.